Combined Inhibition of PDE4 and PI3Kδ Modulates the Inflammatory Component Involved in the Progression of Chronic Obstructive Pulmonary Disease - Dinavahi, S. S.; Nyayapathy, S.; Perumal, Y.; Dharmarajan, S.; Viswanadha, S. (Drug Research, 2014)
Chronic Obstructive Pulmonary Disease (COPD) represents a group of disorders with several underlying causes that hamper airflow into the lungs. Despite current intervention therapies, COPD remains a disease with a significant unmet medical need. Treatment with Phosphodiesterase (PDE) 4 inhibitors results in modest efficacy at clinically relevant doses. The objective of the current study is to evaluate the combination of a PDE4 (Roflumilast) and a Phosphoinositide-3-kinase (PI3K) δ (IC87114) inhibitor for their therapeutic potential in diminishing the inflammatory response associated with COPD. Due to their divergent and independent pathways, we hypothesize that the combination would be efficacious at low concentrations in an in vitro setting. Inhibition of TNFα, pAkt, MMP-9 in differentiated U937 macrophages upon stimulation with LPS/CSE was determined. Neutrophil functionality manifested by a modulation of elastase activity was estimated. Protective effect of drug combination on CSE induced apoptosis of lung epithelial cells was also determined. Data demonstrated that the combination of Roflumilast and IC87114 reduced TNFα, pAkt and MMP-9 at nanomolar concentrations and was several fold potent than either of the compounds alone. Inhibition of neutrophil elastase was also increased significantly with the combination along with a better protection against CSE induced apoptosis in alveolar epithelial cells, thereby providing a rationale for their evaluation in COPD patients.
Keywords: COPD; Roflumilast; IC87114; PDE4; PI3Kδ